OP0122 Fine Mapping of the CHR 22Q13.1 Juvenile Idiopathic Arthritis Risk Locus. (9th June 2015) - Moncrieffe, H.; Lele, A.; Shams, K.A.; Levy, B.E.; Marion, M.; Sudman, M.; Brungs, L.; Cobb, J.; Hinks, A.; Bohnsack, J.; Wedderburn, L.R.; Haas, J.-P.; et al.
Abstract : Background: Juvenile Idiopathic Arthritis (JIA) patients have arthritis onset of unknown cause that lasts >6 weeks in the inflamed joints of children younger than 16 years. JIA is a complex genetic trait with established increased familial risk and robustly replicated genetic associations (e.g. HLA, PTPN2 ). Multiple single nucleotide polymorphisms (SNPs) in the 22q13.1 locus have reached genome-wide significance in recent genetic association studies using the Immunochip. The 22q13.1 locus contains both IL2RB and RAC2 which are attractive candidates to influence JIA pathology and have respective roles in IL-2 signaling and cell migration. Objectives: To identify the statistically, bioinformatically and experimentally most plausible causal SNPs associated with risk of JIA in the 22q13 region. Methods: We fine mapped the 22q13.1 locus using data from large scale genotyping projects of a European ancestry cohort of subjects with (3, 905) and without JIA (14, 388) to predict variants most likely causal at the 22q13.1 locus. Logistic regression conditional analysis was used to define regions of association followed by Bayesian analysis to define variants with large posterior probabilities. Transcription factor binding predictions were used to identify variants for experimental testing by electrophoretic mobility shift assay (EMSA). We limited our investigation to polyarticular RF - and oligoarticular JIA cases to reduce phenotypic heterogeneity. Results: Conditional analyses showed independent associations to JIA in both the IL2RB and RAC2 loci. We identified two SNPs that can account for all of the JIA genetic association in this region. Using a Bayesian analysis we identified the SNPs that explained 95% of the posterior probability in the region and are the most likely to be causal. Altered nuclear extract binding was observed with risk and non-risk alleles in the IL2RB locus but not RAC2. These experimental data are consistent with the predicted alteration in transcription factor binding. Conclusions: Polymorphic variants in the RAC2 and the nearby IL2RB locus are independent JIA risk loci. Use of the statistical and bioinformatics approach to produce candidates for laboratory validation is an important strategy in defining the function of risk variants in JIA. Disclosure of Interest: None declared